Presence of Belowground Neighbors Activates Defense Pathways at the Expense of Growth in Tobacco Plants - Chen, Bin J. W.; Hajiboland, Roghieh; Bahrami-Rad, Sara; Moradtalab, Narges; Anten, Niels P. R. (Frontiers in Plant Science, 2019)
Plants can detect the presence of their neighbors belowground, often responding with changes in root growth for resource competition. Recent evidence also implies that perception of neighbors may also elicit defense responses, however, the associated metabolic activities are unclear. We investigated primary and defense-related secondary metabolisms and hormone expressions in tobaccos (Nicotiana rustica) grown either with own roots or roots of another conspecifics in hydroponic condition. The results showed that non-self root interaction significantly reduced photosynthetic activity and assimilate production, leading to a reduction of growth. Non-self interaction also modified plant phenylpropanoids metabolism, yielding higher lignin content (i.e. structural resistance) at whole plant level and higher phenolics accumulation (i.e. chemical defense) in roots. All these metabolic responses were associated with enhanced expressions of phytohormones, particularly jasmonic acid, salicylic acid and cytokinin in roots and abscisic acid in leaves, at the early stage of non-self interaction. Since the presence of neighbors often increase the probability of attacks from e.g. pathogens and pests, this defense activation may act as an adaptation of plants to these possible upcoming attacks.